Investigating Students Reading Habit and Preferences : A Case Study in English Eduacation Undergraduate Students of University Bina Bangsa Getsempena - Erika Fitriani; Mulyadi Syahputra; Rizka Marlisa Aini (Jurnal Pendidikan dan Sastra Inggris, 2026)
This study examines the reading habits and reading preferences of students in the English Language Education program at Bina Bangsa Getsempena University. Reading habits and reading preferences play an important role in developing students’ academic literacy and supporting their academic success. This study aims to describe students’ reading habits and identify the reading materials they prefer. The research design used is a descriptive qualitative case study. The study participants consisted of 103 undergraduate students. Data were collected via a questionnaire and analyzed descriptively by presenting frequencies and percentages. The findings indicate that most students have fairly consistent reading habits, typically reading for 30–60 minutes, two to three times a week, primarily during their free time or for academic purposes. The results also show that students prefer digital reading materials over print materials. Fiction and fantasy, romance, and adventure are the most preferred genres, while scientific articles, textbooks, and educational books remain the primary academic reading materials. These findings suggest that students’ reading preferences are influenced by personal interests and academic needs. This study concludes that universities should encourage balanced reading habits by providing engaging academic and non-academic reading resources.